Relevance of the pyroptosis-related inflammasome drug targets in the Chuanxiong to improve diabetic nephropathy - ChangYan Li; JingYuan Ma; Niroj Mali; Le Zhang; Tao Wei; LuYao Shi; Fang Liu; Fan WenXing; Jing Yang (BMC, 2022)
Abstract Background A chronic inflammatory disease caused by disturbances in metabolism, diabetic nephropathy (DN) is a chronic inflammatory disease. Pyroptosis is a novel form of programmed cell death in many inflammation-related diseases, including DN. Therefore, pyroptosis could be a promising target for DN therapy. Methods To get the components and pharmacodynamic targets of Chuanxiong, we identified by searching TCMID, TCMSP, ETCM and HERB databases. Then, from the Molecular Signatures Database (MSigDB) and Gene Ontology (GO) database, pyroptosis genes were collected. Identification of critical genes in DN by bioinformatics analysis and then using the ConsensusClusterPlus package to divide the express data of diff genes into some subgroups with different levels of pyroptosis; the WGCNA machine algorithm was used to simulate the mechanism Chuanxiong improving DN. Results In this study, we found DHCR24, ANXA1, HMOX1, CDH13, ALDH1A1, LTF, CHI3L1, CACNB2, and MTHFD2 interacted with the diff genes of DN. We used GSE96804 as a validation set to evaluate the changes of APIP, CASP6, CHMP2B, CYCS, DPP8, and TP53 in four different cell proapoptotic states. WGCNA analysis showed that DHCR24, CHI3L1, and CACNB2 had significant changes in different cell proapoptotic levels. In the experimental stage, we also confirmed that the active ingredients of Chuanxiong could improve the inflammatory state and the levels of pyroptosis under high glucose. Conclusion The improvement of DN by Chuanxiong is related to the change of pyroptosis.